Simultaneous determination of nine tyrosine kinase inhibitors in three complex biological matrices by using high‐performance liquid chromatography–diode array detection combined with a second‐order calibration method. Issue 21 (12th September 2021) - Wang, Zhao‐Yang; Wu, Hai‐Long; Chang, Yue‐Yue; Wang, Tong; Chen, Wei; Tong, Gao‐Yan; Yu, Ru‐Qin
Abstract: An intelligent chemometric second‐order calibration method called alternating trilinear decomposition‐ assisted multivariate curve resolution combined with high‐performance liquid chromatography–diode array detection was used for the simultaneous quantification of nine tyrosine kinase inhibitors in three complex biological systems. The method allows simultaneous quantification of the components in different biological matrices without the need for cumbersome pre‐treatment steps, complex elution conditions, and complete peak separation. Even with the varying time shift, severe peak overlap, and various unknown interferences, the proposed method can extract pure chromatographic and spectroscopic information for each analyte, while providing accurate qualitative and quantitative results of nine common tyrosine kinase inhibitors in three different biological matrices. All the drugs were eluted in 7 min. The results showed that the nine drugs in each matrix showed good linearity ( r  > 0.984) in the calibration range with a root mean square error of calibration less than 0.9 μg/mL. The average spiked recoveries of the target analytes were all in the range of 83.4–110.0%, with standard deviations less than 9.0%. Finally, the classical method was used to validate the proposed method. In comparison to the traditional method, the proposed strategy is accuracy, simultaneous, and interference‐free.